Biobased epoxy vitrimer from epoxidized soybean oil for reprocessable and recyclable carbon fiber reinforced composite. (December 2020) - Liu, Yu-Yao; He, Jia; Li, Yi-Dong; Zhao, Xiao-Li; Zeng, Jian-Bing
Abstract: Traditional carbon fiber reinforced epoxy thermosets composites are nonrenewable and cannot be reprocessed or recycled due to the permanent crosslinked structure of the thermosets, causing resource crisis, environmental pollution, and resource waste. Herein, a biobased epoxy vitrimer (ESO-VA) with dynamic Schiff base groups was synthesized from epoxidized soybean oil (ESO), vanillin, and 4-aminophenol. The biobased epoxy vitrimer showed excellent malleability, recyclability, and mechanical properties, making it suitable as matrix to fabricate carbon fiber (CF) reinforced composites. The CF fabric reinforced ESO-VA composites showed superior mechanical strength and modulus over ESO-VA. The composites can be recycled through different approaches, owning to the dynamic Schiff base unit. The valued CF fabric can be recycled without changing structure and properties by deconstruction network structure of ESO-VA as a result of dissociation of Schiff base bond under acidic condition. The composites after crushing could be recycled thermally into short carbon fiber filled composite products through traditional processing techniques such as compression molding. We believe that this study provides a strategy to design recyclable carbon fiber reinforced biobased epoxy composites. Highlights: Biobased epoxy vitrimer was synthesized from epoxidized soybean oil and vanillin. The biobased epoxy vitrimer can be used as a matrix for carbon fiber reinforced composites. Carbon fiber reinforced vitrimer composite showed excellent recyclability and reprocessability.